FILSAFAT ILMU SEBAGAI LANDASAN PENGEMBANGAN MODEL MANAJEMEN BERBASIS KETANGKASAN DAN KETAHANAN - Siagian, Supriadi; Hidayah, Taufiq; Purwanto, Purwanto; Mujiatun, Siti (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study explores the pivotal role of philosophy of science as an ontological, epistemological, and axiological foundation in developing organizational management models based on agility and resilience amid 21st-century VUCA uncertainties. Through a qualitative reflective approach employing conceptual systematic literature review, the research synthesizes fragmented management literature, revealing that agility represents the dynamic essence of organizations as adaptive social systems,, while resilience embodies value-oriented sustainability preserving core identity and long-term purpose. Epistemological pluralism integrates empirical data, tacit knowledge, and contextual reflection, transcending instrumental paradigms. Compared to prior studies focused on operational metrics, this framework offers deeper philosophical reflection, addressing research gaps in ethical and existential dimensions. Theoretical contributions include an integrated tri-dimensional matrix linking philosophy to adaptive capabilities, enriching management discourse. Practical implications urge balanced agility-resilience practices for Indonesian MSMEs and public sectors, emphasizing value-embedded decision-making. Limitations encompass the conceptual nature lacking empirical validation, suggesting future mixed-methods testing across cultural contexts. This work pioneers a normative paradigm shift, positioning philosophically grounded models as essential for sustainable organizational thriving in turbulent environments.. Keywords: Philosophy of Science, Organizational Agility, Organizational Resilience, Management Model, Sustainability. Abstrak: Penelitian ini mengkaji peran fundamental filsafat ilmu sebagai landasan ontologis, epistemologis, dan aksiologis dalam pengembangan model manajemen organisasi berbasis ketangkasan dan ketahanan di tengah ketidakpastian VUCA abad ke-21. Melalui pendekatan kualitatif reflektif dengan desain systematic literature review konseptual, kajian mensintesis literatur manajemen yang terfragmentasi, mengungkap ketangkasan sebagai esensi ontologis organisasi sebagai sistem sosial adaptif, sementara ketahanan mencerminkan orientasi aksiologis keberlanjutan nilai yang mempertahankan identitas inti dan tujuan jangka panjang. Pluralisme epistemologis mengintegrasikan data empiris, pengetahuan tacit, dan refleksi kontekstual, melampaui paradigma instrumental. Dibandingkan studi terdahulu yang berfokus metrik operasional, kerangka ini tawarkan refleksi filosofis mendalam, mengisi kesenjangan dimensi etis-eksistensial. Kontribusi teoretis mencakup matriks tiga dimensi terintegrasi yang hubungkan filsafat dengan kapabilitas adaptif, memperkaya wacana manajemen. Implikasi praktis dorong praktik seimbang ketangkasan-ketahanan bagi UMKM dan sektor publik Indonesia, dengan pengambilan keputusan berbasis nilai. Keterbatasan bersifat konseptual tanpa validasi empiris, sarankan pengujian mixed-method lintas konteks budaya ke depan. Kajian ini mempelopori paradigma normatif baru, memposisikan model berlandaskan filsafat sebagai esensial bagi keberlanjutan organisasi di lingkungan turbulen. Kata kunci: Philosophy of Science, Organizational Agility, Organizational Resilience, Management Model, Sustainability.